Mistress or slaves? Drifts of lesbian desire between Armando Bo and Manuel Puig (2023)
The following pages present a joint reading marked by lesbian desire of a passage from the film Fuego (Armando Bo, 1969) and a fragment of the novel Pubis angelical (Manuel Puig, 1979). It is proposed to critically address the construction of erotic relationships between female characters in light of the theoretical contributions of gender studies as well as practices and reflections from the archive, in order to unravel the inscriptions, meanings and scope around the lesbian desire housed in each fiction. The purpose is listening the dialogue between both authors, a space in which unregulated identifications and identities are put into operation.